Impact of social media on triggering nonsuicidal self-injury in adolescents: a comparative ambulatory assessment study - Goreis, Andreas; Chang, Dorothy; Klinger, Diana; Zesch, Heidi-Elisabeth; Pfeffer, Bettina; Oehlke, Sofia-Marie; Ebner-Priemer, Ulrich; Claes, Laurence; Plener, Paul L.; Kothgassner, Oswald D. (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Nonsuicidal self-injury (NSSI) is a prevalent and concerning behavior among adolescents, often triggered by negative interpersonal events. As social media is essential in the daily life of adolescents, gaining a better understanding of the impact of negative online events on NSSI urges and behaviors, distinct from that of real-life events, is warranted.